Anatomical variations of the popliteal artery as a risk factor for its laceration during total knee arthroplasty: controversies with illustrative case report - Boljanović, Jelena; Glišić, Miodrag; Ilijevski, Nenad; Bećirović, Matija; Stojanović, Smiljana; Pavković, Ivana; Djurdjević, Katarina; Blagojević, Valentina (Vojnosanitetski pregled, 2025)
Introduction. Popliteal artery (PA) injury during knee replacement surgery is a rare but extremely serious complication. Most vascular complications during knee surgery can be prevented by a careful preoperative assessment of the patient. Case report. We present the case of a 51-year-old woman who was admitted to the hospital to undergo routine total knee arthroplasty (TKA) surgery due to rheumatoid arthritis. The patient underwent surgery via standard medial parapatellar approach under spinal anesthesia. A fixed-bearing implant was used. The operation was successfully performed, but after removing the tourniquet, excessive bleeding was encountered, indicating a possible injury to the PA, hence the tourniquet was placed again. Severed PA was noted after exploration of the popliteal region, while the posterior capsule was not damaged. Revascularization with a Dacron vascular graft was performed immediately. On the third day following surgery, the patient had complaints that caused a suspicion of graft occlusion, and she was transferred to the Clinic for Cardiovascular Surgery. Multidetector computed tomography angiography confirmed total occlusion of the popliteal Dacron graft, and surgery was performed. The occluded graft was removed, and a popliteal-tibioperoneal trunk bypass was performed using an autologous great saphenous vein graft. Lateral and posterior fasciotomies were performed as well. At the three-month follow-up examination, the patient remained asymptomatic, with improvement in ankle dorsiflexion function. Conclusion. Preoperative assessment can help identify patients who are at the highest risk of complications of PA during their TKA. If vascular complications occur, early recognition and immediate intervention by a vascular surgeon are essential for a positive treatment outcome.